2012
DOI: 10.1111/j.1749-6632.2012.06551.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and functional heterogeneity of human bone marrow– and amnion‐derived MSC subsets

Abstract: Bone marrow-derived mesenchymal stromal/stem cells (MSCs) are nonhematopoietic cells that are able to differentiate into osteoblasts, adipocytes, and chondrocytes. In addition, they are known to participate in niche formation for hematopoietic stem cells and to display immunomodulatory properties. Conventionally, these cells are functionally isolated from tissue based on their capacity to adhere to the surface of culture flasks. This isolation procedure is hampered by the unpredictable influence of secreted mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 87 publications
4
58
0
Order By: Relevance
“…Color images available online at www.liebertpub.com/scd surface marker profile to av-MSCs. Both cell types lack expression of MSCA-1 and CD271, which have been suggested as markers for an especially clonogenic subpopulation of bone marrow MSCs [24][25][26][27]. While MSCA-1 and AP are known to be only expressed by bone-marrow-derived MSCs [24], the expression of CD271 has been described in a small subpopulation of av-MSCs before [17].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Color images available online at www.liebertpub.com/scd surface marker profile to av-MSCs. Both cell types lack expression of MSCA-1 and CD271, which have been suggested as markers for an especially clonogenic subpopulation of bone marrow MSCs [24][25][26][27]. While MSCA-1 and AP are known to be only expressed by bone-marrow-derived MSCs [24], the expression of CD271 has been described in a small subpopulation of av-MSCs before [17].…”
Section: Discussionmentioning
confidence: 98%
“…MSCs are commonly identified via the expression of specific surface markers, including CD73, CD105, and CD90 and lack the expression of various immune cell and ECs markers, such as CD45, CD14, HLA-DR, and CD34 [2,22]. In our analysis we included additional markers known to be expressed by MSCs [23,24]. bv-MSCs express most of these markers and have a very similar FIG.…”
Section: Discussionmentioning
confidence: 99%
“…15 This finding was later confirmed by Sivasubramaniyan and coworkers, who furthermore identified CD56 as a positive marker for endosteally localized MSCs. 48 Regarding differences in CFU-F potential, Mabuchi et al demonstrated that single CD271…”
Section: But Not In the Cd271mentioning
confidence: 99%
“…MSCs are known to participate in the formation of niches for HSC development in the bone marrow. Several markers, including CD106, CD166, CD105, CD73 and CD44, are known to be useful in the isolation of MSCs from various organs, including bone marrow, placenta, adipose tissue, synovial membrane, endometrium and cartilage (53). The construction of niche-like regions during EMH may be attributed to the MSC-derived cells of EMH organs, although CXCL12-positive cells were only identified in the red pulp of EMH-positive sinus endothelial cells (19).…”
Section: Microenvironment Of Emhmentioning
confidence: 99%